2021
DOI: 10.1002/cpt.2382
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Stimulates Intestinal Glycolysis and Lactate Release: A single‐Dose Study of Metformin in Patients With Intrahepatic Portosystemic Stent

Abstract: The pharmacodynamic and pharmacokinetic properties of metformin translate poorly from animal models to humans. In humans, metformin increases intestinal uptake of glucose tracers, but the fate of glucose is unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…The effects of an acute, single-dose of metformin on the plasma metabolome has been investigated. Rittig et al ( 46 ) reported that 90 min after patients with cirrhosis had taken 1000 mg of metformin, tricarboxylic acid (TCA) cycle intermediates were elevated suggesting increased tissue glycolysis, along with decreased microbiome-derived metabolites linked to benzoate and hippurate metabolism. Others have found significant changes in pathways linked with valine, leucine and isoleucine biosynthesis, phenylalanine metabolism, and FA metabolism after healthy males were given 500 mg of metformin ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of an acute, single-dose of metformin on the plasma metabolome has been investigated. Rittig et al ( 46 ) reported that 90 min after patients with cirrhosis had taken 1000 mg of metformin, tricarboxylic acid (TCA) cycle intermediates were elevated suggesting increased tissue glycolysis, along with decreased microbiome-derived metabolites linked to benzoate and hippurate metabolism. Others have found significant changes in pathways linked with valine, leucine and isoleucine biosynthesis, phenylalanine metabolism, and FA metabolism after healthy males were given 500 mg of metformin ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence indicate that the gastrointestinal tract is involved in the acute anti-hyperglycemic effect of metformin (Bailey et al, 2008; Koffert et al, 2017; Ma et al, 2022; Rittig et al, 2021). In accordance, we observed that metformin increased glucose clearance by ~75% in the proximal part (duodenum and jejunum) of the intestine (Figure 2G) that displayed ~10- and 70-fold higher metformin concentrations compared to the liver and muscle, respectively (Figure 2H).…”
Section: Resultsmentioning
confidence: 99%
“…In accordance, we observed that metformin increased glucose clearance by ~75% in the proximal part (duodenum and jejunum) of the intestine (Figure 2G) that displayed ~10- and 70-fold higher metformin concentrations compared to the liver and muscle, respectively (Figure 2H). Following uptake into the intestine, glucose is directed through glycolysis to form lactate since metformin increases anaerobic glucose metabolism in the intestine (Bailey et al, 2008; Rittig et al, 2021). This likely contributes to increased blood lactate levels that are associated with regular metformin use (Bailey and Turner, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations